Analysis of the Users’ Understanding of Icons in Graphical User Interface of Simorgh Software - Mohammad-Javad Hashemzadeh; Masoumeh Yeganehfar (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2010)
Purpose: This research is devoted to study the icons in graphical user interface of Simorgh library software and analyze the users’ understanding of and interaction with this software in Birjand University. Methodology: The methodology of this research is of survey type and it is an applied study. To measure the responders’ understanding of icons in different pages of search section in Simorgh software, 32 icons from four pages of search section which were available to the population under study were chosen and put into a questionnaire. Both descriptive and deductive statistics methods were utilized for data analysis. Findings: According to five-level Likert scale, the user’s perspective regarding the three elements of significance level, observing the criteria to be user-friendly, and quality of icons in graphical user interface of Simorgh software were evaluated to be higher than average, higher than average, and medium, respectively. Besides, users’ general understanding of these icons was 38.5% which has a significant difference compared to the desired level of understanding (60%). No significant difference was observed among understanding of the icons by users of different educational level; however, users’ understanding of icons in different pages in search section of this software was not identical. Furthermore, educational field and experience of users in using the graphical interface of Simorgh software influenced the level of understanding of these icons. Originality/Value: Through designing a questionnaire for evaluating the level of understanding of icons in Simorgh library software based upon mentioned elements as well as making use of existing literature and experts’ opinion, the present study has provided the opportunity for those involved in library software development to alleviate the weaknesses and reinforce the strengths; also, they can better get acquainted with existing criteria in this field and their importance to make use of them in their future products.